2022
DOI: 10.1021/acs.orglett.2c01734
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium-Catalyzed Cyclization to Dihydrobenzo[c]phenanthridinone from 7-Azabenzonorbornadienes with Aryl Amides

Abstract: An efficient ruthenium(II)-catalyzed tandem C−C/C−N bond formation with aryl amides and 7azabenzonorbornadienes has been developed to synthesize cis-fused dihydrobenzo[c]phenanthridinones. The amide group functions as a directing group as well as a leaving group and provides an easy access to the pharmaceutically useful benzo[c]phenanthridine alkaloids such as nitidine and fagaronine analogues. The present methodology is compatible with various functional groups with respect to azabicyclic alkenes and aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
0
15
1
Order By: Relevance
“…mechanistic pictures of the CpCo-catalyzed ARO reactions where cisand trans-β-oxygen elimination work as the selectivity-determining step for enantioselective and racemic reactions, respectively. Such results are different from the previous cognition 47,[53][54][55][56][57][58][59][60][61][62][63][64] . As an extension, 7-azabenzonorbornadiene could also be applied in the similar ARO reactions in a diastereodivergent manner.…”
contrasting
confidence: 97%
See 2 more Smart Citations
“…mechanistic pictures of the CpCo-catalyzed ARO reactions where cisand trans-β-oxygen elimination work as the selectivity-determining step for enantioselective and racemic reactions, respectively. Such results are different from the previous cognition 47,[53][54][55][56][57][58][59][60][61][62][63][64] . As an extension, 7-azabenzonorbornadiene could also be applied in the similar ARO reactions in a diastereodivergent manner.…”
contrasting
confidence: 97%
“…1b) [47][48][49] . Merging ARO reactions with transition-metal-catalyzed C-H activation has become an area of recent interest [50][51][52][53][54][55][56][57][58][59][60] . In this regard, the groups of Zheng and Li 53 , and Cramer 54 independently reported the ARO reactions of 7-azabenzonorbornadienes and other aza-bicyclic olefins under Rh-catalysis, in which β-nitrogen elimination was a key step.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jeganmohan et al 17 recently reported an intriguing method to synthesize pharmaceutically relevant dihydrobenzo[ c ]phenanthridinones through Ru-catalyzed hydroarylation of arylamides and 7-azabenzonorbornadienes. The amide group in the substrate can effectively act as both the leaving group and the directing group.…”
Section: Ru-catalyzed Hydroarylation-classificationmentioning
confidence: 99%
“…In the vast majority of C–H functionalizations, removing the amide directing group requires additional steps. 12 To date, there are only a few examples of catalytic cyclization using amide as a directing group and a leaving group, 13 and they are limited to tertiary aromatic amides. To our knowledge, cyclization reactions based on the merger of α-C–H and C–N activation of amides have not yet been realized.…”
mentioning
confidence: 99%